Upaya Meningkatkan Motivasi dan Hasil Belajar IPA Siswa Melalui Penerapan Model Pembelajaran STAD di Kelas Vi SD Negeri 42 Mataram - Ni Luh Purwati (Jurnal Paedagogy, 2019)
This study aims to determine the effectiveness of the application of STAD learning models in an effort to improve science learning motivation of Class VI students at SD Negeri 42 Mataram. This research method uses classroom action research conducted in two cycles, each cycle of activities is; planning, implementation, observation and reflection. The final results of the action in the second cycle showed that the results of teacher observation obtained an average score of 4.50 and the results of student observations reached an average score of 4.14. While the impact of increased learning motivation is the increase in student learning outcomes reaching an average value of 90.77, meaning that indicators of success> 4.0 have been exceeded. Because the indicators of success have been proven, the research was declared successful and stopped in the second cycle.